Gross Morphological Studies on the Mammary Gland of Malnad Gidda Cows of Karnataka - Ganga Naik, S. (Indian Journal of Veterinary Anatomy, 2020)
Present work was carried out to study the gross morphological features of mammary gland of Malnad Gidda cows. It is located external to the body cavity, bowl shaped, bilaterally symmetrical organ, which was suspended from the in-guinal region by suspensory ligaments and other tissues. The udder comprised of four individual mammary glands. Each quarter was having glandular body and one principal teat with a single open-ing.The mammary gland of malnad gidda cow was covered by thin, easily-movable skin over the underlying fascia except on the teats where it was bound to the deeper layers of the wall. It bears sparse thin hairs.Theindividual glands were referredas quarters. These quarters were located in the left and right halves. The left and right halves of the udder are separated by alongitudinal groove called intermammary groove.This corresponds to median septum of connective tissue dividing into left and right halves.The boundary between the fore and hindquarters of the same side were separated indicating the two quarters in each half were separated from one another as far as the gland tissue and duct system was concerned. The left fore quarter was smaller in its size as compared to that of left hind quarter, but the alveolar branching pattern were similar in both the side. The gland cistern receives about ten lactiferous ducts in Malnad Gidda cows. There are two supramammary lymph nodes located in theposterolaterapart of the mammary gland in these cows.